Comparison of lightweight and traditional figure skating blades, a prototype blade with integrated damping system and a running shoe in simulated figure skating landings and vertical countermovement jumps, and evaluation of dampening properties of the prototype blade - Spiegl, O.; Tarassova, O.; Lundgren, L. E.; Neuman, D.; Arndt, A. (Sports Biomechanics, 2025)
To date, there is no empirical evidence suggesting greater jump heights or cushioned landings when using figure skating (FS) blades of different mass and design. This study examined the effect of lightweight (Gold Seal Revolution from John Wilson) and traditional (Apex Supreme from Jackson Ultima and Volant from Riedell) blades, a new prototype blade with an integrated damping system (damping blade) in two different damping configurations, and running shoes (Runfalcon from Adidas) on kinetics and kinematics during simulated on-ice landings from 0.6 m and maximal countermovement jumps on synthetic ice, and measured dampening properties of the damping blade. Seventeen participants executed trials in the six footwear conditions blinded to the different blades and acted as their own control for statistical comparison. There were no differences between the lightweight and traditional blades on the maximal vertical ground reaction force during the landing. Image analysis showed a damping effect in the damping blade that significantly decreased the landing load for all participants (mean 4.38 ± 0.68 bodyweight) (p = 0.006), on average between 10.1 and 14.3% compared to lightweight and traditional blades (4.87 ± 1.01 to 5.11 ± 0.88 bodyweight). The maximal jump height achieved was the same in all FS blades.